Simultaneous Genotyping of Three SNVs, rs5471, rs5472, and rs2000999 Involved in Serum Haptoglobin Levels by Fluorescent Probe‐Based Melting Curve Analysis - Soejima, Mikiko; Koda, Yoshiro (Electrophoresis, 2024)
ABSTRACT Haptoglobin (Hp) is a hemoglobin‐binding acute‐phase serum protein. Several single nucleotide variations (SNVs) within the Hp gene (HP) or Hp‐related protein gene (HPR), such as rs5471 (A > C) and rs5472 (A > G) in HP promoter region and rs2000999 (G > A) in intron 2 of HRP, are suggested to correlate with the serum Hp levels. To determine these three SNVs simultaneously, a genotyping assay based on duplex dual‐labeled fluorescent probes was developed. The method was then validated by analyzing genomic DNA from 121 Ghanaian and two Japanese subjects who had been previously genotyped for rs5471, rs5472, and rs2000999. Both rs5471 and rs5472 could be determined as haplotypes with a single FAM‐labeled fluorescent probe, and rs2000999 could be genotyped with a HEX‐labeled fluorescent probe. The results obtained with the present method were consistent with the previous results except for those of three Ghanaian subjects. All three subjects appear to have multiple HPR copy number variants characteristic of African populations, which may have led to incorrect results during previous genotyping. This method allows us to genotype these three SNVs in a relatively large number of samples, especially in African populations where rs5471 is uniquely distributed.